43 Large Grafting Session (Hair Transplantation, 2023)
Large balding areas are best treated with large strip surgeries. Complications such as widened scars and poor growth can be avoided if the surgeries are performed with precision. Ideas to minimize scalp damage during strip harvest and recipient site prep will be outlined.
Keywords: donor laxity; minimizing scalp damage; sharp recipient blades; maintaining intact vasculature